Describing about ‘Teachers and Kemuhammadiyahan’ in elementary School Department: A review of literature - Elihami Elihami (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Islamic movements are known as Muhammadiyah. KH. A. Dahlan created Amar Makruf Nahi Munkar, an Islam aqidah rooted from the Qur'an and Sunnah, on the 8th of Dhulhijjah 1330 H, which corresponds to the date of November 18th, 1912 Miladiyah in Yogyakarta. Muhammadiyah's goal is to enforce and defend Islam's faith in order to build a true Islamic community. The efforts and actions of Muhammadiyah can be divided into four categories: 1) The religious field, which entails providing direction and recommendations in the areas of faith, worship, morals, and mu'amalah. 2) Education program, which comprises education aimed at bridging the gap between general education and schooling. 3). The domains of social community, which comprise activities such as hospital, polyclinic, dispensary, and orphanage philanthropic works.